Long‐term outcomes for children and adolescents with Kaposi sarcoma. Issue 2 (11th October 2021) - Silverstein, Allison; Kamiyango, William; Villiera, Jimmy; Peckham‐Gregory, Erin C.; McAtee, Casey L.; Scheurer, Michael E.; Cox, Carrie M.; Kovarik, Carrie L.; Campbell, Liane R.; Allen, Carl E.; Mehta, Parth S.; Kazembe, Peter N.; et al.
Abstract: Objectives: Kaposi sarcoma (KS) is one of the most common childhood cancers in eastern and central Africa. It has become a treatable disease with increasing availability of antiretroviral therapy (ART) and chemotherapy. We aimed to fill the data gap in establishing whether long‐term survival is achievable for children in low‐income countries. Methods: We retrospectively analysed data for children and adolescents aged ≤ 18.9 years diagnosed with HIV‐related or endemic KS from 2006 to 2015 who received standardized institutional treatment regimens utilizing chemotherapy plus ART (if HIV‐positive) at a tertiary care public hospital in Lilongwe, Malawi. Long‐term survival was analysed and mortality was associated with KS for those with refractory/progressive disease at the time of death. Results: There were 207 children/adolescents with KS (90.8% HIV‐related); 36.7% were alive, 54.6% had died, and 8.7% had been lost to follow‐up. The median follow‐up time for survivors was 6.9 years (range 4.2–13.9 years). Death occurred at a median of 5.3 months after KS diagnosis (range 0.1–123 months). KS progression was associated with mortality for most (61%) early deaths (survival time of < 6 months); conversely, KS was associated with a minority (31%) of late‐onset deaths (after 24 months). The 7‐year overall survival was 37% [95% confidence interval (CI) 30–44%] and was higher for those diagnosed between 2011 and 2015 compared to 2006–2010: 42% (95% CI 33–51%) versus 29% (95% CI 20–39%), respectively ( P = 0.01). Among the 66 HIV‐positive survivors, 58% were still on first‐line ART. Conclusions: Long‐term survival is possible for pediatric KS in low‐resource settings. Despite better survival in more recent years, there remains room for improvement.